Change in Mortgage Taxation in New York in 1906 - Fetter, Frank A. (Quarterly Journal of Economics, 1906)
Journal Article Change in Mortgage Taxation in New York in 1906 Get access Frank A. Fetter Frank A. Fetter Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 20, Issue 4, August 1906, Pages 613–616, https://doi.org/10.2307/1882725 Published: 01 August 1906